Dança como fator potencialmente modificável nas demências: efeitos de um treinamento de dança sobre marcadores cognitivos e capacidade física em mulheres idosas - Silva, Tamires Vicente (Universidade Federal de São Carlos, 2025)
The exponential growth of the older adult population and the increasing burden of cognitive health–related problems demand the development and implementation of effective strategies to promote healthy, autonomous, and active aging. In this context, dance has emerged as a potential intervention to address cognitive health challenges and mitigate impairments that may accompany the aging process, acting as a modifiable factor associated with dementia risk. Therefore, it is essential to investigate approaches that promote physical, cognitive, and emotional health in older adults, contributing to improvements in quality of life and overall well-being. Objective: To evaluate the effects of a three-month dance-based intervention in older women, considering anthropometric, physical, metabolic, cognitive, and psychological outcomes. Methods: This was a pre–post intervention study with a single dance intervention group (n = 34). Physical assessments, body composition analyses, questionnaires assessing cognitive status and emotional well-being, and measurements of biochemical parameters and ADAM10 levels were conducted. Heart rate was monitored during the sessions to ensure maintenance of moderate-intensity exercise. Intervention effects were analyzed using linear mixed-effects models. Results: Body composition analysis indicated a trend toward reduced fat mass (–3.2%; p = 0.063; d = 0.065). Significant improvements were observed in metabolic parameters, including reductions in triglycerides (–16.1%; p = 0.012; d = 0.460) and fasting glucose (–8.2%; p < 0.001; d = 0.780). Cognitive performance improved significantly, with increases in immediate memory (+11.1%; p < 0.001; d = 0.767) and delayed memory (+31.7%; p < 0.001; d = 0.761), as well as a trend toward higher Mini-Mental State Examination scores (+3.1%; p = 0.062; d = 0.102). Depressive symptoms decreased significantly (–30.1%; p = 0.010; d = 0.48). Conclusion: These findings suggest that dance may be incorporated as an effective non-pharmacological intervention to promote metabolic and cognitive health in older women, demonstrating potential to reduce modifiable factors associated with the risk of dementia development.
Dance as a potentially modifiable factor in dementia: effects of a dance training program on cognitive markers and physical capacity in older women
Keywords: Cognição; Dança; Intervenção não Farmacológica; Mulheres Idosas; Cognition; Dance; Non-pharmacological Intervention; Older Women; CIENCIAS DA SAUDE::EDUCACAO FISICA; 3. Saúde e Bem-Estar